(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Differentiated thyroid carcinoma (DTC) is among the most prevalent endocrine malignancies, with a rising global incidence. Since 1980, the Thyroid Division of the National Institute of Nuclear Medicine and Allied Sciences (NINMAS), Bangladesh Atomic Energy Commission (BAEC), has been treating DTC patients with Radioactive Iodine Therapy (RAIT) following thyroidectomy and maintaining lifelong follow-up. To date, over 9,000 patients have received RAIT, generating a vast volume of medical records that have been preserved exclusively as hardcopies, creating significant space and retrieval challenges. This project aims to digitally archive both medical records and BRAF mutation genomic sequencing data of all radioiodine-treated DTC patients, encompassing records from 1980 to the present. Approximately 4,000 patient records have been digitized so far, using dedicated software, specialized hardware, and individual patient ID systems. Among them, 15 high-risk patients underwent BRAF gene sequencing, of which 10 tested positive. Digital archiving has demonstrably improved clinical efficiency, enabling faster data retrieval, better longitudinal patient management, and a robust foundation for future oncological research. Continuation of this initiative will ensure comprehensive registration of all remaining DTC patients. Bangladesh J. Nuclear Med. 28(2): 241-246, July 2025